Menelisik Nikah Beda Agama di Indonesia dalam Kajian Yuridis Normatif - Asman (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
Interfaith marriages are raised in a public discussion space so that it makes you curious to review until now there is no point of contact and there are still those who marry different beliefs, so that the statutory regulations that have been determined or stipulated are pros and cons in the opinion of academics. This research uses a normative juridical approach as normative legal research. This research is to describe the problems in the literature review in the analysis in the concept of the review of the Marriage Law and the analysis of the concept in the review of Islamic law. And in this discussion the focus is on: What is the perspective of Islamic law on marriage with different faiths? What is the perspective of national law on marriage with different faiths? The results of this research are First, the principles of fiqh conclude that interfaith marriages can lead to apostasy for Muslims, Second, in the maqashid syariah principle it is better to avoid interfaith marriages for the benefit of personal and family benefits.Third, in Islamic principles it prohibits different marriages. belief, as described in the Koran in surah al-Maidah verse 5.